IMPLEMENTASI DELAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SEBAGAI UPAYA PENCEGAHAN PENYAKIT SEJAK DINI DI SEKOLAH DASAR - Pramadhani, Wulan; Hulmansyah, Danil; Olivia, Annisa; Putri, Naiza Amelia (LPPM Universitas Awal Bros, 2025)
Clean and Healthy Living Behavior (PHBS) is a fundamental habit that should be instilled from an early age, especially among school-aged children. This educational activity aims to improve students' knowledge and attitudes toward the importance of CHLB both at school and at home. The methods used include lectures, discussions, hands-on practice, as well as pre-tests and post-tests for evaluation. The results showed that most students experienced an increase in awareness and had begun to implement most CHLB indicators effectively. This activity demonstrates that a participatory educational approach can successfully foster sustainable healthy living behaviors